(3dWGFa GdEQTGOGJ aj MbGFb GdYHGQGJ aj JaSjQ GdbQBfs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s ((3GHh Ydi YHO Gddg Hf SYO Hf YHO Gddg Hf SYOs)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM bdhH ChdjGFg dYQaGfg hcJGHfG jCJi Ydi XQa ef GTGQGJ GdbQGf Ydi dSGf Ggd GdeYQaI aGJMI GdcJGH gPg GdShQI JSei aGJMI GdcJGH s
(3BNQgG (B:s
(3hdGjTQc HYHGOI QHg hdG jTcQ WGYJg hdjJHQC ef Mhdg hbhJg hGdMeO ddg QH GdYGdejf Je GdeLdO GdChd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
Keywords: (3GdJaSjQ hYdhe GdbQBfs